Morphological Variations Species of Ziziphus (Rhamnaceae) in Java - Ihsan, Moh.; Azrianingsih, Rodiyati; Rugayah, Rugayah; Efendi, Muhammad (Universitas Brawijaya, 2022)
Ziziphus in Indonesia, especially Java, hasfive species recorded in the book Flora of Java. In 2010, there were two additional species that had not been recorded in the Flora of Java. Some species of unresolved taxon position and nomenclature are valid and precise. Meanwhile, the latest scientific journal publications related to taxonomic studies of Ziziphus species in Java have not been widely carried out and are even almost non-existent. This study aimedto re-examine the Ziziphus species in Java based on variations in morphological characters. Exploration and identification of specimens throughout Java and herbarium study specimens were carried out. The morphological characterizations observed included stature, morphology of stems, leaves, flowers, fruits, and seeds. The identification obtained eight species, Ziziphus mauritiana Lam., Ziziphus spina-christi (L.)Desf., Ziziphus celtidifolia DC., Ziziphus javanensis Blume, Ziziphus horsfieldii Miq., Ziziphus rufula Miq., Ziziphus oenoplia (L.) Mill. and Ziziphus nummularia (Burm. f.) Wight et Arn. Three species of which are new records for the Java region, among others; Ziziphus celtidifolia DC., Ziziphus mauritiana Lam. and Ziziphus spina-christi (L.) Desf. Phenetic analysis based on morphological characteristics showed that Ziziphus in Java had 52% -81% similarity.